Developing Islamic sustainable finance framework for Islamic Banks: Tawhidi String Relation (TSR) approach. - Budiharjo, Anas; Ismail, Nor Asmat; Rahim, Hainnuraqma (Journal of Islamic, Social, Economics and Development, 2025)
The critique of Islamic banks has shifted from emphasis on contracts (aqd) to the role of Islamic banks in creating a real economy to improve the well-being of society and the environment as a whole. Unfortunately, Islamic banks lack a mechanism to meet those objectives. Therefore, some countries oblige Islamic banks to adopt a sustainable finance model based on the Environmental, Social, and Governance (ESG) framework despite its origins in conventional financial systems. Nevertheless, based on previous studies, most Muslim scholars believe the ESG is an imperfect framework for Islamic banks. They suggest Islamic banks develop a suitable framework to ensure investments and other financial services realize maqasid al-Shariah, especially concerning ESG aspects. Therefore, this paper aims to identify sustainable finance issues from an Islamic perspective and then develop an Islamic sustainable finance framework for Islamic banks using the Tawhidi String Relation (TSR) approach. The study adopts a qualitative research methodology. A comprehensive literature review and content analysis are used to identify the issue and to develop the framework. The study's significant result is the development of a new Islamic Sustainable Finance framework or ISF. This study identified al-‘Alwani’s theory of Maqasid al-‘Ulya al-Hakimah, combined with the explanation (sharah) of his student, Malkawi, as the most suitable framework for Islamic banks to achieve sustainability. It consists of five components: (1) Tawhid, (2) Tazkiya of the human self, (3) Tazkiya of wealth, (4) Tazkiya of society, (5) Development (umran) of the earth. This framework addresses all parts of human well-being. Operationalizing the five components of the proposed framework will achieve the transition from the theoretical framework to practical application.